Gαs-Coupled CGRP Receptor Signaling Axis from the Trigeminal Ganglion Neuron to Odontoblast Negatively Regulates Dentin Mineralization - Natsuki Saito; Maki Kimura; Takehito Ouchi; Tatsuya Ichinohe; Yoshiyuki Shibukawa (Biomolecules, 2022)
An inflammatory response following dental pulp injury and/or infection often leads to neurogenic inflammation via the axon reflex. However, the detailed mechanism underlying the occurrence of the axon reflex in the dental pulp remains unclear. We sought to examine the intracellular cyclic adenosine monophosphate (cAMP) signaling pathway in odontoblasts via the activation of Gs protein-coupled receptors and intercellular trigeminal ganglion (TG) neuron–odontoblast communication following direct mechanical stimulation of TG neurons. Odontoblasts express heterotrimeric G-protein α-subunit Gαs and calcitonin receptor-like receptors. The application of an adenylyl cyclase (AC) activator and a calcitonin gene-related peptide (CGRP) receptor agonist increased the intracellular cAMP levels ([cAMP]i) in odontoblasts, which were significantly inhibited by the selective CGRP receptor antagonist and AC inhibitor. Mechanical stimulation of the small-sized CGRP-positive but neurofilament heavy chain-negative TG neurons increased [cAMP]i in odontoblasts localized near the stimulated neuron. This increase was inhibited by the CGRP receptor antagonist. In the mineralization assay, CGRP impaired the mineralization ability of the odontoblasts, which was reversed by treatment with a CGRP receptor antagonist and AC inhibitor. CGRP establishes an axon reflex in the dental pulp via intercellular communication between TG neurons and odontoblasts. Overall, CGRP and cAMP signaling negatively regulate dentinogenesis as defensive mechanisms.